Analisis Penerapan Sustainability Aspek Sosial terhadap Kinerja Keuangan pada Perusahaan Kelapa Sawit yang Terdaftar pada Gabungan Pengusaha Kelapa Sawit Indonesia (GAPKI) - Sihotang, Yoshua; Situmorang, Aston L. (Universitas Methodist Indonesia, 2026)
This research aims to analyze the implementation of social aspect disclosures in sustainability reports and their relationship with financial performance in GAPKI member companies during 2021-2023. Out of 20 companies that published annual reports and sustainability reports, only 13 consistently reported for three consecutive years and were therefore used as research samples. The research method employed is quantitative with an exploratory approach. Financial performance was analyzed using Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The results show that most companies have achieved a high level of disclosure, with the majority reaching 100% (fully applied) in 2023. However, the increase in disclosure did not align with a consistent pattern in financial performance, as the financial ratios tended to fluctuate. These findings indicate that the implementation and disclosure of the social aspect in sustainability reports serve more to enhance accountability, transparency, and corporate image, while their direct relationship with financial performance has not been clearly observed.